National Plan of Recovery and Resilience and Digitalization of Public Administrations: New Opportunities for Old Challenges for Social Work - Zenarolla, Anna (Italian Sociological Review, 2023)
The object of this paper is to encourage contemplation on the opportunities and problems the contemporary digital era presents for social work. Due to the rapid adoption of digitalization in Public Administrations mandated by National Plan of Recovery and Resilience and National Social Plan 2021-2023, it is important to keep in mind a number of theoretic and methodological tenets in order to avoid reducing social service digitalization to a purely technical issue and to make the most of the opportunities it presents for social work in order to successfully adapt to the specific approach and intervention goals. The reflection is based on observations made while monitoring the creation and implementation of the Friuli Venezia Giulia Region’s Informational System for Social Services (ISSS) and the digitization of the Cartella Sociale, used by social workers across all the region’s social services. The paper highlights the significance of considering ISSS not just as a tool for gathering information describing reality but, more importantly, as a tool for its users to advance their knowledge and build relationships with their client and one another. Due to this, it suggests concentrating the informational tools and systems on social workers’ daily tasks and developing them with their direct and ongoing engagement.